2000
DOI: 10.1023/a:1009599208790
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: This paper revisits a developmental model of the origins of early conduct problems. Several of the model's primary tenets have now been validated in two samples of at-risk children followed prospectively from infancy to school-age. In both cohorts, child, family, and sociodemographic factors all play a significant role in the development of early conduct problems. In particular, the quality of the caregiving environment during the child's second year differentiates clinical impairment according to both parent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
104
0
2

Year Published

2006
2006
2015
2015

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 200 publications
(113 citation statements)
references
References 45 publications
7
104
0
2
Order By: Relevance
“…Research has demonstrated that coercive, harsh, and overcontrolling parenting during early childhood contributes to adjustment difficulties during elementary school, including CPs (e.g., Campbell, Shaw, & Gilliom, 2000; McFadyen-Ketchum, Bates, Dodge, & Pettit, 1996; Shaw, Owens, Giovannelli, & Winslow, 2001). Of particular importance to our study are the results of the review by Shaw, Bell, and Gilliom (2000), who concluded that the quality of the caregiving environment at age 2 significantly predicted clinical-level elevations of CPs reported by caregivers and teachers 6 years later. This relationship might be more salient for children with more difficult to control behaviors (e.g., Shaw et al, 1994; Shaw et al, 1998).…”
Section: Early Coercion and School Adjustmentmentioning
confidence: 90%
“…Research has demonstrated that coercive, harsh, and overcontrolling parenting during early childhood contributes to adjustment difficulties during elementary school, including CPs (e.g., Campbell, Shaw, & Gilliom, 2000; McFadyen-Ketchum, Bates, Dodge, & Pettit, 1996; Shaw, Owens, Giovannelli, & Winslow, 2001). Of particular importance to our study are the results of the review by Shaw, Bell, and Gilliom (2000), who concluded that the quality of the caregiving environment at age 2 significantly predicted clinical-level elevations of CPs reported by caregivers and teachers 6 years later. This relationship might be more salient for children with more difficult to control behaviors (e.g., Shaw et al, 1994; Shaw et al, 1998).…”
Section: Early Coercion and School Adjustmentmentioning
confidence: 90%
“…Indeed, highly reactive, difficult temperamental traits in children appear to do as much to elicit characteristic patterns of detached parental conduct as vice versa (Shaw, Bell, & Gilliom, 2000;Stoolmiller & Snyder, 2004). The hypothesis about psychopathy as a life history strategy implies that children would not be passive recipients, but would exhibit traits that maximize survival.…”
Section: The Selectionist Hypothesismentioning
confidence: 99%
“…Negative discipline strategies such as physical interference and a predominance of simple prohibitions at the cost of positive alternatives are also related to child externalizing problems in early childhood, in particular in the context of child difficult temperament (Van Zeijl et al 2007) or maternal insensitivity (Alink et al (2009)). Maternal insensitivity in itself has also been found to predict early childhood externalizing problems (e.g., NICHD 2004; Shaw et al 2000). According to Ainsworth and her colleagues (Ainsworth et al 1974), children are naturally motivated to comply with their parents' rules when parents are sensitive and responsive.…”
Section: Introductionmentioning
confidence: 99%